La nuit pensée et vécue comme une frontière quasi topologique - Jean-Pierre Desclés (Ateliers d'Anthropologie)
The notions “night”, “day”, “sunset”, “sunrise”, “dawn” and “dusk” have meanings that are not independent, since they are part of frameworks structured by a quasi-topology, which is an extension of the general topology. To a place, the quasi-topology links its interior and strict interior, its closure and large closure, its internal and external boundaries, its simple boundary and large boundary... To analyse the notion of “night”, I consider two interpretive quasi-topological models. The first model is organised around two opposite places, night and day—sunset and sunrise being the boundaries that separate these two places. The second model is organised around the two places that are sunset (descent and disappearance of the sun) and sunrise (appearance and ascent of the sun), night being a quasi-topological large (non-punctual) boundary, where various inversions take place. This second model makes it possible to structure the inversions of nocturnal activities encountered in certain cultures (particularly in Mesoamerican cultures).